2021
DOI: 10.2478/sjph-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of four-dimensional oral health problems across dental fields – A comparative survey of Slovenian and international dentists

Abstract: Objectives To compare the frequency of patients’ oral health problems and prevention needs among Slovenian and international dentists with the aim to validate the four oral health-related quality of life (OHRQoL) dimensions across six clinical dental fields in all World Health Organization (WHO) regions. Methods An anonymous electronic survey in the English language was designed using Qualtrics software. A probability samplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some studies have concluded that patients with chewing muscle pain are more prone to stress and depression [ 16 , 17 ]. Stress and anxiety are the well-known psychological factors that correlate with TMD because stress can cause muscle hyperactivity, resulting in symptoms of TMD [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have concluded that patients with chewing muscle pain are more prone to stress and depression [ 16 , 17 ]. Stress and anxiety are the well-known psychological factors that correlate with TMD because stress can cause muscle hyperactivity, resulting in symptoms of TMD [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%